An automated approach for predicting glioma grade and survival of LGG patients using CNN and radiomics - Xu, Chenan; Peng, Yuanyuan; Zhu, Weifang; Chen, Zhongyue; Li, Jianrui; Tan, Wenhao; Zhang, Zhiqiang; Chen, Xinjian (Frontiers in Oncology, 2022)
Objectives: To develop and validate an efficient and automatically computational approach for stratifying glioma grade and predicting survival of lower-grade glioma(LGG) patients using an integration of state-of-the-art convolutional neural network(CNN) and radiomics. Method: This retrospective study reviewed 470 preoperative MR images of glioma from BraTs public dataset(n=269) and Jinling hospital (n=201). A fully automated pipeline incorporating tumor segmentation and grading was developed, which can avoid variability and subjectivity of manual segmentations. First, an integrated approach by fusing CNN features and radiomics features was employed to stratify glioma grade. Then, a deep-radiomics signature based on the integrated approach for predicting survival of LGG patients was developed and subsequently validated in an independent cohort. Results: The performance of tumor segmentation achieved a Dice coefficient of 0.81. The intraclass correlation coefficients (ICCs) of the radiomics features between the segmentation network and physicians were all over 0.75. The performance of glioma grading based on integrated approach achieved the area under the curve (AUC) of 0.958, showing the effectiveness of fusion of CNN features and radiomics features. The multivariable Cox regression results demonstrated that the deep-radiomics signature remained an independent prognostic factor and the integrated nomogram showed significantly better performance than the clinical nomogram in predicting overall survival of LGG patients (C-index: 0.859 vs. 0.760, P=0.002). Conclusion: The proposed integrated approach can be noninvasively and efficiently applied in prediction of gliomas grade and survival. Moreover, our fully automated pipeline successfully achieved computerized segmentation instead of manual segmentation, which shows the potential to be a reproducible approach in clinical practice.